Tenebrio molitor reared on different substrates: is it gluten free?. (April 2020) - Mancini, Simone; Fratini, Filippo; Tuccinardi, Tiziano; Degl'Innocenti, Chiara; Paci, Gisella
Abstract: Mealworm ( Tenebrio molitor ) is one of the most interesting insects studied as feed and food. Usually, mealworms are reared in a close environment in constant contact with their feed, called substrate. Mostly of the substrates employed for mealworms rearing, used alone or as an ingredient in a feed mix, contain gluten. Therefore, the aim of this work was to evaluate if gluten could be vehiculate by the mealworms from the substrate into the final product. T. molitor larvae were fed different substrates that naturally contain or not contain gluten. Determination of gluten was then performed on the substrates and the larvae. Furthermore, larvae were washed and/or starved in order to quantify if these rearing procedures could decrease the potential gluten content. As main result gluten was detected in the larvae in a direct relation to the gluten content of the substrates. Washing and fasting decreased the quantity of gluten highlighting that it was present on the surface of the mealworms and in their gut. After washing and fasting procedures all the samples, without differences on the substrate fed, revealed a gluten content below 20 ppm (gluten free product). Anyhow, caution is needed as the final risk of contamination is not zero, therefore, testing the mealworms for gluten presence is advised. Highlights: Mealworms were reared on substrates with different gluten contents. Gluten was determined both in substrates and larvae. Larvae were washed and/or fasted. Mealworms might carry gluten from the substrates. Washing and fasting practises could decrease health risks.